Educational resources’ status as determinants of students’ learning outcomes in senior secondary school government in Oyo State, Nigeria (2014)
Over the years, issues of poor academic performance of students both in examinations have been of grave concern to all stakeholders in the education industry. This study investigated the relationship between all categories of educational resources (human, financial and material resources) and Senior Secondary School students' learning outcomes in Government in Oyo State. The study is a survey research that adopted multi-stage sampling technique. Data were collected from 450 SSS II Government students and 30 teachers from 30 public and private schools in Oyo State. Four research questions and two validated instruments guided the study with reliability coefficient of 0.67 for SERI and 0.86 for GAT. Data were analyzed using descriptive statistics, Pearson Product Moment Correlation and Multiple Regression. Results revealed that human resources were reportedly the most available 300 (66.7%), while financial resources were the least obtainable educational resources in the secondary school. The rates of utilisation revealed that 271 (60.2%) respondents admitted to using available resources most times. Results further indicated that there were moderate relationships between availability and adequacy of utilisation of the various educational resources and students' learning outcome (r = 0.64). The three predictor variables jointly accounted for 62% (Adjusted R2 = 0.621) observed variance in students' learning outcome in Government as it was statistically significant. It is recommended that all stakeholders in the school system should ensure availability, usability and adequacy of all educational resources since they all predict students' learning outcomes and ensure that they are always utilised optimally in the teaching-learning processes.